Creative industry development in Sidoarjo Regency from a community perspective - Munari - Kustanto (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2022)
The creative industry is one of the sectors most prepared to face today's increasingly dynamic environmental changes. The existence of the community plays an important role in the development of creative industries in an area, including in Sidoarjo Regency. This study aims to analyze the challenges faced by the community in developing creative industries in Sidoarjo Regency as well as to formulate efforts to develop creative industries. Using a qualitative approach, this study utilizes primary data obtained through FGDs as well as secondary data in its analysis. The results show that from a community perspective, the development of creative industries in Sidoarjo Regency faces several challenges related to the mindset of the community and creative industry players, difficulties in accessing banking, unattractive packaging, inadequate supporting infrastructure, weak marketing, and the availability of resources both raw materials and raw materials. man. The development of the creative industry of the tourism population in Sidoarjo Regency demands an important role from the government both as a facilitator and regulator, so that it becomes a catalyst for pentahelix actors. Creative industry development strategies can be carried out through providing educational training and curriculum, encouraging the formation of the non-banking sector, and expanding networks.